Commercial anti‐CD19 CAR T cell therapy for patients with relapsed/refractory aggressive B cell lymphoma in a European center. Issue 11 (25th August 2020) - Sesques, Pierre; Ferrant, Emmanuelle; Safar, Violaine; Wallet, Florent; Tordo, Jérémie; Dhomps, Anthony; Karlin, Lionel; Brisou, Gabriel; Vercasson, Marlène; Hospital‐Gustem, Carole; Schwiertz, Vérane; Ranchon, Florence; et al.
Abstract: Two autologous anti‐CD19 chimeric antigen receptors (CAR) T cells (axicabtagene ciloleucel [axi‐cel] and tisagenlecleucel [tisa‐cel]) are commercially approved in Europe for relapsed/refractory (R/R) diffuse large B cell lymphoma (DLBCL). We performed a retrospective study to evaluate patterns of use, efficacy and safety for axi‐cel and tisa‐cel. Data from 70 patients who underwent apheresis for commercial CAR T cells between January 2018 and November 2019 in our institution were retrospectively collected. Sixty‐one patients were infused. The median age at infusion was 59 years old (range 27‐75 years). The median number of prior therapies was 3 (range, 2‐6). The overall response rates (ORRs) at 1 month and 3 months were 63% and 45%, respectively, with 48% and 39% achieving a complete response (CR), respectively. After a median follow‐up after infusion of 5.7 months, the median progression‐free survival (PFS) was 3.0 months (95% CI, 2.8‐8.8 months), and the median overall survival (OS) was 11.8 months (95% CI, 6.0‐12.6 months). In multivariate analysis, factors associated with poor PFS were the number of previous lines of treatment before CAR T cells (≥4) ( P = .010) and a C reactive protein (CRP) value >30 mg/L at the time of lymphodepletion ( P < .001). Likewise, the only factor associated with a shorter OS was CRP >30 mg/L ( P = .009). Cytokine release syndrome (CRS) of any grade occurred in 85% of patients, including 8% of patients with CRS of grade 3 or higher. Immune cell‐associated neurotoxicity syndrome (ICANS) of any grade occurred in 28% of patients, including 10% of patients with ICANS of grade 3 or higher. Regarding efficacy and safety, no significant difference was found between axi‐cel and tisa‐cel. This analysis describes one of the largest real‐life cohorts of patients treated with axi‐cel and tisa‐cel for R/R aggressive B cell lymphoma in Europe.